Body composition variables by sport and sport-position in elite collegiate athletes - Fields, J. B.; Merrigan, J. J.; White, J. B.; Jones, M. T. (The Journal of Strength and Conditioning Research, 2018)
To assess body composition measures by sport and sport-position. Elite collegiate athletes participated (n = 475): men's and women's soccer (MSOC, n = 67; WSOC, n = 110); men's and women's swimming (MSWIM, n = 26; WSWIM, n = 22); men's and women's track and field (MTF, n = 29; WTF, n = 24); women's lacrosse and volleyball (WLAX, n = 84; WVB, n = 73); and baseball (BASE, n = 40). One-way analysis of variances assessed differences across sport and sport-position. Post hoc analysis was Tukey honestly significant difference (p = 0.05). For men, BASE and MSWIM had the highest body fat percentage (BF%) (BASE: 16.3 ± 5.2%; MSWIM: 14.2 ± 3.5%). MSOC (11.5 ± 5.3%, 0.13 ± 0.72 kg) and MTF (9.8 ± 5.1%, 0.11 ± 0.08 kg) had the lowest BF% and fat mass (FM)-to-fat-free mass (FFM) ratio (FM:FFM). Fat mass did not differ between MSOC (9.1 ± 4.9 kg), MTF (7.7 ± 5.9 kg), and MSWIM (11.1 ± 3.1 kg). Fat mass for MSOC and MTF was lower than BASE (14.1 ± 5.2). For women, WVB displayed the highest BF% (25.4 ± 5.1%), FM (18.5 ± 5.2 kg), FFM (53.3 ± 5.1 kg), and body mass (BM) (71.8 ± 8.4 kg), but did not differ from WSWIM in BF%, FM, FFM, and BM. WTF had the lowest BF% (12.9 ± 4.0%), FM (7.5 ± 2.5 kg), BM (58.2 ± 4.4 kg), and FM:FFM (0.15 ± 0.05 kg). VB had the highest FFM (53.3 ± 5.1 kg). Body composition differences were observed between sport-positions (p < 0.01). Body composition differed across sport and sport-position, which may be attributed to sport-specific physiological demands.